Aktivno vključevanje deležnikov v upravljanje zavarovanih območij: primer mokrišča Krajinski park Sečoveljske soline - Smrekar, Aleš (Geografski vestnik, 2023)
This article focuses on introducing the concept of participatory management of protected areas using the example of the Sečovlje Salina Nature Park. It is based on the process of creating a voluntary agreementor memorandum to protect a wetland. Using a variety of approaches, we studied, engaged, and encouraged diverse stakeholders in the area to identify conservation, agricultural, and tourism challenges and solutions. Based on territorial workshops with stakeholders, various scenarios were developed, resulting in a wetland conservation memorandum of understanding. This established a core set of voluntary commitments among sixteen key stakeholders for sustainable management of the Sečovlje Salina Nature Park
Keywords: agreement; costal wetlands; geography; Istria; Koprsko primorje; mokrišča; participativni proces; participatory process; protected areas; Sečoveljske soline; Slovenia; Slovenija; sporazum; varstvo okolja; zavarovana območja